Chyluria: what does the clinician need to know?. (July 2020) - Stainer, Victoria; Jones, Patrick; Juliebø, Siri Øvereng; Beck, Rupert; Hawary, Amr
Chyluria is secondary to the presence of chyle in the urine. The classical appearance on inspection is of milky white urine, which is caused by a fistulous communication between the lymphatic system and the urinary tract. Worldwide, it is most commonly associated with the parasite Wuchereria bancrofti, which is prevalent in Asia, most extensively in India but also China and Taiwan. However, in the United Kingdom, Europe and North America, where the condition is rare, non-parasitic aetiologies predominate. Chyluria is occasionally associated with other urinary tract symptoms including infection, loin pain and haematuria. It may also cause hypoproteinaemia, weight loss and cachexia. Management is based on identifying the aetiology and depends on the severity of the chyluria and presence of associated symptoms. Given its predominate symptom being urinary, cases in the West can fall under the care of the urologist. The aim of this article is to provide an overview and summary of the aetiology, assessment and management of chyluria based on the most up-to-date evidence available. This was achieved through a non-systematic review of world literature.